2013
DOI: 10.1111/srt.12067
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold capillaroscopy in systemic sclerosis: Is there any difference between videocapillaroscopy and dermatoscopy?

Abstract: We suggest that dermatoscopy is efficient enough to identify pathognomonic changes in NCP in SSc as well as VCAP and find dermatoscopy as a very easy applicable and convenient method than VCAP although VCAP facilitates a more detailed evaluation of NCP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 13 publications
4
16
0
1
Order By: Relevance
“…The training needed for the device is minimal (∼5 days ) and the required examination time is short (∼10 minutes including image recording). An NVC apparatus is more costly than handheld devices such as dermatoscopes, but NVC has been shown to permit more‐detailed assessments and the grading of more images . During patient follow‐up, detailed assessment and quantification of abnormalities is important, and therefore, handheld tools may not be as useful in this setting .…”
Section: Discussionmentioning
confidence: 99%
“…The training needed for the device is minimal (∼5 days ) and the required examination time is short (∼10 minutes including image recording). An NVC apparatus is more costly than handheld devices such as dermatoscopes, but NVC has been shown to permit more‐detailed assessments and the grading of more images . During patient follow‐up, detailed assessment and quantification of abnormalities is important, and therefore, handheld tools may not be as useful in this setting .…”
Section: Discussionmentioning
confidence: 99%
“…Fortuitously, there are a number of low cost and handheld devices such as dermatoscopes and ophthalmoscopes which achieve a good visualisation of the nailfolds at around 10-20-fold magnification (see Figure 2c). A number of studies directly comparing these techniques with WSM and NVC have found a reassuring concordance [10][11][12]. In particular, although the rate of "unclassifiable" images is higher, ample diagnostically relevant findings can be elicited, even if more subtle changes can be missed.…”
Section: Handheld Devices-ophthalmoscopes Dermatoscopes Usb Microscmentioning
confidence: 90%
“…Dogan et al . compared the diagnostic value of dermoscopy and videocapillaroscopy for determining nailfold capillary pattern changes in patients with SSc, and concluded that dermoscopy was efficient in recognizing the pathognomonic changes …”
Section: Discussionmentioning
confidence: 99%
“…7 Dogan et al compared the diagnostic value of dermoscopy and videocapillaroscopy for determining nailfold capillary pattern changes in patients with SSc, and concluded that dermoscopy was efficient in recognizing the pathognomonic changes. 24 We used a videodermatoscope with 9 30 magnification, and easily recognized the nailfold capillary changes in patients with BD, thus we recommend videodermoscopy for evaluating such changes. However, NVC can only evaluate most features of capillary morphology qualitatively, except for capillary density, which could be measured quantitatively.…”
Section: Discussionmentioning
confidence: 99%